2019
DOI: 10.3390/cells8121659
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotype and Secretory Activity of Adipose-Derived Mesenchymal Stem Cells (ASCs) of Patients with Rheumatic Diseases

Abstract: Mesenchymal stem/stromal cells (MSCs) have immunosuppressive and regenerative properties. Adipose tissue is an alternative source of MSCs, named adipose-derived mesenchymal stem cells (ASCs). Because the biology of ASCs in rheumatic diseases (RD) is poorly understood, we performed a basic characterization of RD/ASCs. The phenotype and expression of adhesion molecules (intracellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1) on commercially available healthy donors (HD), ASC lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 57 publications
4
30
1
Order By: Relevance
“…Although preconditioning can alter various MSCs activities, its final outcome depends on the type of applied priming factor and combination of some of them, e.g., TNFα and IFNγ exerts usually additive effects 41 . We have previously reported that TI treatment upregulates ICAM-1, but not VCAM-1, expression on ASCs and increases secretion of some (kynurenines, IL-6, and LIF), while fails to modify release of other (IL-1Ra, sHLA-G, TSG-6, galectin-3, and TGFβ) immunoregulatory factors, pointing out some selectivity of TI priming 10 . Importantly, untreated (naïve) MSCs are endowed with some immunoregulatory activities as well, including regulation of T-cell activation markers expression 44 , 46 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although preconditioning can alter various MSCs activities, its final outcome depends on the type of applied priming factor and combination of some of them, e.g., TNFα and IFNγ exerts usually additive effects 41 . We have previously reported that TI treatment upregulates ICAM-1, but not VCAM-1, expression on ASCs and increases secretion of some (kynurenines, IL-6, and LIF), while fails to modify release of other (IL-1Ra, sHLA-G, TSG-6, galectin-3, and TGFβ) immunoregulatory factors, pointing out some selectivity of TI priming 10 . Importantly, untreated (naïve) MSCs are endowed with some immunoregulatory activities as well, including regulation of T-cell activation markers expression 44 , 46 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 92%
“…Thus, MSCs use various mediators to keep T-cell activation under control. Identification of factors implicated in presently observed ASCs effects exerted on T lymphocytes requires further studies, but our previous comparative characteristics of HD/ASCs and RD/ASCs secretory activity point out some candidates, including TGFβ 10 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This Special Issue covers research articles investigating various adipose tissues as a source for ASC isolation [ 1 , 2 , 3 ], specific cultures methods to enhance proliferation or viability [ 4 , 5 , 6 , 7 ], and the differentiation capacity [ 8 , 9 , 10 , 11 , 12 ]. Furthermore, other studies highlight aspects of various diseases [ 13 , 14 ], the immunosuppressive potential of ASCs and their derivates [ 15 ] or the in vivo tracking of transplanted ASCs [ 16 ].…”
mentioning
confidence: 99%
“…A study by Plava and co-workers identified that ASCs are permanently altered in the presence of tumor breast tissue and have the potential to increase tumor cell invasive ability through the activation of epithelial-to-mesenchymal transition in tumor cells [ 13 ]. Another study characterized ASCs isolated from patients with rheumatoid arthritis and described their altered phenotype and secretory activity compared to ASCs from healthy donors [ 14 ].…”
mentioning
confidence: 99%